Consumers' preference and consumption towards fast food: evidences from Malaysia / Farzana Quoquab Habib , Rozhan Abu Dardak , Sabarudin Zakaria - Habib, Farzana Quoquab; Abu Dardak, Rozhan; Zakaria, Sabarudin (Faculty of Business Management, 2011)
This study aims to understand consumer preference relating to the fast food in Malaysian market. Moreover, this paper seeks to investigate the trend and pattern of fast food consumption and the importance of various factors affecting the choice of fast food among Malaysian consumers. Findings suggest that expenditure for fast food mostly goes to fried chicken, while instant noodles are the least. Moreover, food safety, speed in delivery and food taste suitability has been found as the main influential factors for purchasing the fast food. On the contrary, quality, freshness, easy to cook, and cleanliness are the second priority. Furthermore, 'Halal' status has been indicated as the most important factor for the Muslim consumers. Survey method using convenience sampling has been carried out for conducting this study. Therefore, further research targeting a more diverse group of consumers employing random sampling can provide greater generalization.